Collaboration between Asian countries in materials, chemistry, life and food science, information technology, electric, civil engineering, architecture and mechanical engineering. - Mat Arip, Yahya
A bacteriophage infecting Pseudomonas aeruginosa USM AR2 was successfully isolated from hydrocarbon-contaminated muddy soil. Morphological study revealed a phage with icosahedral capsid head and long non-contractile tail. The genome of the phage was determined as double stranded DNA. Thus, the phage could be a member of the Siphoviridae family.